Control and Monitoring System for a Three-Phase Induction Motor Based on Arduino Mega and VSD Integrated with LabVIEW - Fahrul Marcello Rombon; Kevind Lefinro Rompas; Natanael Hendriko Lombok; Sukandar Sawidin; Yoice R. Putung; Anthoinete P.Y. Waroh (Jambura Journal of Electrical and Electronics Engineering, 2026)
Three-phase induction motors are widely utilized in industrial applications due to their high efficiency and reliability. This study aims to design and implement a real-time control and operational parameter monitoring system for a three-phase induction motor. The system integrates an Arduino Mega as the main data processor, a Variable Speed Drive (VSD) for speed control, and Solid State Relays (SSR) along with contactors as actuators. Monitoring of electrical and mechanical parameters is performed using ACS712 sensors (current), ZMPT101B sensors (voltage), and Hall Effect sensors (speed/RPM), with the results displayed on a LabVIEW interface. The system evaluation and validation method was carried out by comparing sensor readings against standard measuring instruments (digital multimeter and digital tachometer) across various operating frequency variations. The test results show that the system is capable of stable operation with an average sensor measurement error (mean error) of 0.35%. The novelty of this research lies in the integration of a responsive, cost-effective, multi-parameter control and monitoring platform equipped with automatic data logging within a single integrated HMI interface, which is ready to be applied for research as well as industrial automation laboratory practices.